2009
DOI: 10.1681/asn.2008121258
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Regulation of PTH by Estrogens May Require FGF23

Abstract: The mechanisms by which estrogens modulate PTH are controversial, including whether or not estrogen receptors (ERs) are present in the parathyroid glands. To explore these mechanisms, we combined a rat model of CKD with ovariectomy and exogenous administration of estrogens. We found that estrogen treatment significantly decreased PTH mRNA and serum levels. We did not observe ER␣ or ER␤ mRNA or protein in the parathyroids, suggesting an indirect action of estrogens on PTH regulation. Estrogen treatment signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 54 publications
2
60
2
1
Order By: Relevance
“…Various mechanisms may explain this association, including increased undernutrition with age, decreased renal phosphate reabsorption, and hormonal factors. The association between hyperphosphatemia and female sex has also been reported in many previous studies [19,21,[23][24][25][26][27][28]. Reasons for this association are as yet poorly understood, but some experimental studies have demonstrated that estrogens reduce PTH transcription and vitamin D activation as well as increase FGF-23 circulating levels [29].…”
Section: Discussionmentioning
confidence: 54%
“…Various mechanisms may explain this association, including increased undernutrition with age, decreased renal phosphate reabsorption, and hormonal factors. The association between hyperphosphatemia and female sex has also been reported in many previous studies [19,21,[23][24][25][26][27][28]. Reasons for this association are as yet poorly understood, but some experimental studies have demonstrated that estrogens reduce PTH transcription and vitamin D activation as well as increase FGF-23 circulating levels [29].…”
Section: Discussionmentioning
confidence: 54%
“…All of these factors contribute to regulating the renal tubular phosphate reabsorption capacity and might explain the lower phosphorous excretion observed in women than in men reported by Cirillo and co-workers (27). Furthermore, estrogen circulating levels also modulate bone turnover and calcium and phosphorous bone removal (26). Thus, renal tubular reabsorption and bone removal might account for the difference in serum phosphorous levels and for the paradoxical finding of a lower phosphorous toxicity in women as compared with that in men.…”
Section: Discussionmentioning
confidence: 96%
“…The reasons for such a discrepancy might be explained by the lower basal hazard in women as compared with that in men or, possibly, by the complex interplay between sex hormones and phosphorous homeostasis. Although the mechanisms are not completely understood, experimental studies have demonstrated that estrogens reduce PTH transcription and vitamin D activation as well as increase FGF-23 circulating levels (26). All of these factors contribute to regulating the renal tubular phosphate reabsorption capacity and might explain the lower phosphorous excretion observed in women than in men reported by Cirillo and co-workers (27).…”
Section: Discussionmentioning
confidence: 98%
“…Most studies have found no association between FGF23 and age, but pediatric studies involving very young participants are needed given the differences in phosphorus physiology in infants and toddlers, who manifest markedly higher serum phosphate levels and growth rates than adults. Finally, estradiol stimulates FGF23, 72 and one study reported higher levels in healthy women, 7 but this, too, requires systematic study. Deficiency of klotho, the co-receptor for FGF23, associates with hyperphosphatemia and markedly elevated levels of FGF23.…”
Section: How Do Fgf23 Levels Differ In Specific Ckd Subpopulations?mentioning
confidence: 99%